An investigation of clothing related barriers faced by women with disabilities (Proceedings of the World Disability & Rehabilitation Conference, 2019)
Clothing can serve as a means of conveying to others the equal status in life which disabled women enjoy, as this will promote their self-confidence, self-esteem and make them feel that they are also a part of the community. When taking a holistic approach towards disability rehabilitation and implementation of an acceptable social model in disability care, it becomes apparent that the clothing related issues of women living with disability have not been addressed properly. Therefore it has become an essential need with a high demand among disabled women to fulfil in the current day society. The main objective of the study was to identify the clothing related barriers faced by those women living with disabilities in Sri Lanka and to make recommendations for further research. Semi-structured face-to-face interviews were conducted to identify the clothing barriers. Following the purposive sampling technique, ten respondents were selected. Content analysis technique was used for data analysis. Key barriers were identified and needed adaptive clothing types were categorized based on the women’s activities and daily routine. It was found that the Sri Lankan retail sector did not cater to most of these requirements while adaptive clothing brands did not cater to some of the major problems faced by women with disabilities. Further studies are recommended relating to the development of new adaptive clothing products.
Keywords: Adaptive clothing; Physical disabilities; Women with disabilities